E-076 Imaging to endovascular recanalization in less than an hour is feasible. (4th July 2012) - Almekhlafi, M; Eesa, M; Menon, B; Demchuk, A; Goyal, M
Abstract : Introduction: The shorter the time from core estimation by imaging to recanalization, the more likely that core expansion is minimized. We aimed to assess the feasibility of achieving an ultra-short imaging to recanalization time in the routine practice setting. Methods: This is a prospective, single-operator, case series of acute ischemic stroke patients treated with endovascular therapy in a tertiary center where imaging to recanalization of <60 min was achieved. Results: Imaging to recanalization time <60 min was accomplished in 38% (11 patients) of treated patients. The median imaging to recanalization time was 47 min. The median 24-h NIHSS scale was 1 (range 0–11). Upon discharge, 82% of patients achieved a modified Rankin scale score of 1 or less. Conclusions: An imaging to recanalization time under 60 min is feasible and may be associated with better functional outcome. Competing interests: None.